Тепловая схема замещения мундштука пресса с электрическим обогревом - Ярымбаш, С. Т.; Коцур, И. М. (НТУ "ХПИ", 2005)
The thermal equivalent circuit of a mouthpiece of squeezer with electrical heating is offered. In conjugation by a mathematical model of a resistance heater of a mouthpiece enables to calculate its non-stationary and quasistationary thermal conditions&
Keywords: тепломассоперенос; тепловое сопротивление; ресурсы вычислительные; схема тепловая; теплопроводность